Perianal ultrasound (PAUS): visualization of sphincter muscles and comparison with digital-rectal examination (DRE) in females - Miriam Hölscher; Charlotte Gräf; Anna-Lena Stickelmann; Elmar Stickeler; Laila Najjari (BMC, 2021)
Abstract Background The aim of this study was to determine the reproducibility and tolerance of perianal ultrasound (PAUS) and detect differences in sphincter muscles between various measuring positions and different maneuvers. PAUS was compared to digital-rectal examination (DRE) to see if sphincter contraction is visible and gradable in ultrasound volumes. Methods Fifty women underwent a medical history, DRU and PAUS by two uro-gynecologists in a prospective trial. PAUS volumes were measured via different parameters in different maneuvers. Examiners' DRE impressions of sphincter tone were scaled with the DRESS-score. All patients completed a questionnaire. Results Thirty-five patients with complete PAUS and DRE were included in the study. Fifteen patients were excluded due to poor ultrasound volume quality or sphincter defects. Comparison of sphincter muscle thickness at different positions in PAUS showed significant differences between 6 and 12 o'clock positions (12 > 6 o'clock) and diameters (horizontal > vertical). No difference was found between the examiners. In comparison of rest and contraction only the vertical diameter changed. There was a negative but not significant correlation between PAUS measurements and DRESS-scores. Twenty-six patients completed the questionnaire that revealed women preferred PAUS over DRE. Conclusion PAUS is a reproducible and good tool to visualize the anal canal. It is comfortable for patients and easily handled by examiners. Sphincter muscle contraction is iso-volumetric. Vertical diameter changes during contraction leading the anal canal change its shape to oval due to external influence. PAUS is the ideal additional tool to visualize relevant structures that are palpable on DRE.